Clarithromycin-Induced Long QT Syndrome: A Case Report - Mecnun Cetin; Munevver Yıldırımer; Serkan Özen; Sema Tanrıverdi; Senol Coskun (Case Reports in Medicine)
Long QT syndrome develops for a number of reasons. The number of non-antiarrhythmic drugs reported to induce QT interval prolongation with or without torsade de pointes continues to increase. Clarithromycin is a macrolide antibiotic being increasingly used for the treatment of atypical pneumonia. In this paper, we describe a patient who developed long QT prolongation syndrome after receiving clarithromycin for the treatment of atypical pneumonia.